2020
DOI: 10.3390/pharmaceutics12111068
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Poly(ethylene glycol) and Lipid Structure in Targeted Gene Delivery to Lymph Nodes by Lipid Nanoparticles

Abstract: Targeted delivery of nucleic acids to lymph nodes is critical for the development of effective vaccines and immunotherapies. However, it remains challenging to achieve selective lymph node delivery. Current gene delivery systems target mainly to the liver and typically exhibit off-target transfection at various tissues. Here we report novel lipid nanoparticles (LNPs) that can deliver plasmid DNA (pDNA) to a draining lymph node, thereby significantly enhancing transfection at this target organ, and substantiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 56 publications
(61 reference statements)
0
68
0
Order By: Relevance
“…In our contribution, different types of structured phospholipid vesicles were used as drug delivery systems for potential anticancer therapy to achieve high therapeutic efficiency. Effective accumulation of these nanostructures in target tissues depends on their physicochemical properties such as particle size distribution and surface charge [ 31 ]. Thus, developing safe and stable nanoscopic carriers requires the preparation of monodisperse colloidal systems of a specific size.…”
Section: Resultsmentioning
confidence: 99%
“…In our contribution, different types of structured phospholipid vesicles were used as drug delivery systems for potential anticancer therapy to achieve high therapeutic efficiency. Effective accumulation of these nanostructures in target tissues depends on their physicochemical properties such as particle size distribution and surface charge [ 31 ]. Thus, developing safe and stable nanoscopic carriers requires the preparation of monodisperse colloidal systems of a specific size.…”
Section: Resultsmentioning
confidence: 99%
“…Structurally, reports have shown that using a linear or branched PEG chain can significantly dictate the targeting behaviour and transfection ability of LNPs. Truong group synthesized three LNPs with either Tween 80 (2-[2-[3,5-bis(2-hydroxyethoxy)oxolan-2-yl]-2-(2-hydroxyethoxy)ethoxy]ethyl (E)-octadec-9-enoate), Tween 20 (2-[2-[3,4-bis(2-hydroxyethoxy)oxolan-2-yl]-2-(2-hydroxyethoxy)ethoxy]ethyl dodecanoate) and 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-poly(ethylene glycol) (DSPE-PEG) to encapsulate pDNA and investigate their targeting ability, stability and extent of transfection [ 52 ]. Tween 20 and Tween 80, both non-ionic surfactants are made of saturated carbon tails with similar branched PEG architecture, compared to the linear structure of DSPE-PEG ( Figure 4 ).…”
Section: Lipid-based Nanoparticlesmentioning
confidence: 99%
“…LNPs with the linear DSPE-PEG showed predominantly localized transfection at the injection site. Altogether, this study demonstrated that PEGylation of LNPs with branched PEG is a viable approach to target organs with effective transfection selectively [ 52 ]. It is hypothesized that, aside from the molecular weight and structure, the PEG density on the particle is also an important factor.…”
Section: Lipid-based Nanoparticlesmentioning
confidence: 99%
“… 38 , 47 These studies also assisted in dosimetry development and demonstrating that the intramuscular route of administration generates sufficient inflammatory effects to assist the recruitment of APCs and antigen presentation in regional lymph nodes. 21 , 116 , 117 …”
Section: Short-term Efficacy Studies Confirm the Immunogenicity Of Vamentioning
confidence: 99%